Prevalence and Risk Factors to Preterm Labor through a Study in Jiblah University Hospital, Ibb, Governorate, Yemen - Alsharif, Afaf; Said, Zainab; Mokabes, Fatima; Ameen, Leena; Alqadri, Alya; Musaed, Thekra; Musaed, Bushra; Ahmed, Ala’a; rigih, Halaa (Journal of Community Medicine and Health Solutions, 2025)
Background: Preterm Birth (PTB) is the largest direct cause of neonatal mortality and the second leading cause of under-five mortality following pneumonia. Although there are studies conducted before, the magnitude of PTB remains a major issue in most developing countries including Yemen. Therefore, this study aims to assess the prevalence and associated factors of premature birth among newborns delivered in Jiblah University Hospital in Ibb governorate, Yemen. Objectives: No studies have previously been conducted about preterm labour in Jiblah University Hospital in Ibb governorate, Yemen. Methods: This retrospective observational study was conducted in the Department of Obstetrics & Gynecology, Jiblah University Hospital in Ibb Governorate, from 1 December 2023 to 29 February 2024. Results: A total of 1350 pregnancies, 252 (18.67%) were preterm deliveries and 1089 (80.66%) were full-term deliveries at Jiblah University Hospital, Ibb. Our study shows the distribution of participants based on socio-demographic factors. The data that out of the total 252 female participants, with ages mean ± std = 27.43 ± 6.34 roughly 18.67% experienced preterm deliveries. Our study demonstrates that several factors are significantly linked to preterm birth, including the number of siblings, blood pressure, gravida, and abortion number, where the Chi-square p - value was < 0.05. On the other hand, the results from the logistic regression analysis indicated the predictive potential of certain socio-demographic factors in relation to preterm birth. Conclusion: In this study, the number of siblings, blood pressure, gravida, and abortion number are the risk factors for premature delivery. Recognizing the most common risk factors for PTB will help to increase awareness about high-risk pregnancy, improve the preventive measures of preterm risk factors, and modify preterm care protocol in nurseries.